Analysis of the safety and efficacy of microwave ablation of several foci of multiple lung metastases from colorectal cancer - Bohan Song; Jinfeng Bai; Jinmei Zhou; Yinshan Yang; Qijie Wu; Ming Huang; Hongjie Fan; Xianshuo Cheng; Ping Liu; Yu-Dong Xiao; Xin Zhao; Chongying Deng; et al. (Frontiers in Oncology)
ObjectiveThis study aims to retrospectively analyze the safety and effectiveness of microwave ablation (MWA) in treating multiple lung metastases from colorectal cancer. Additionally, it seeks to compare the superiority of single multiple ablation and fractionated multiple ablation for unilateral lung multiple metastases.Materials and methodsRetrospective analysis was conducted on clinical and pathological data of 82 patients with such multiple lung metastases from colorectal cancer treated from January 2020 to December 2022. Patients were categorized based on the number of MWA sessions required,Patients who had received only one MWA treatment were included in the single MWA group, and patients who had received two or more MWA treatments were included in the multiple MWA group. Chest-enhanced CT scans were performed at 1, 3, 6, and 12 months post-MWA to assess ablation outcomes. The primary focus was the median overall survival (mOS), while secondary endpoints encompassed median progression-free survival (mPFS), technical success rates, and safety. Analysis was performed by log-rank test and Cox proportional hazard regression model, using the Common Terminology Standard for Adverse Events (version 5.0) to assess safety within 28 days after MWA.ResultsThere were 82 patients with numerous lung metastases from colorectal cancer, and they had a total of 182 lesions. These patients underwent 112 microwave ablation (MWA) treatments. Each patient received at least two MWA treatments for their target lesions. The overall median overall survival (mOS) time for all patients was 25 months, the median progression-free survival (mPFS) time was 21 months. No deaths or severe adverse events occurred as a result of the treatment. The univariate Cox regression analysis indicated that fractional MWA (P=0.007) were adverse prognostic factors for CRC patients with lung metastasis.Upon accounting for various confounding factors, the significance of MWA times (P=0.006) remained pertinent in its association. Furthermore, the group that underwent single MWA showed a superior mOS compared to the group that underwent fractionated MWA (P=0.004).ConclusionMicrowave ablation proves to be a safe and efficacious treatment modality for colorectal cancer-associated multiple pulmonary metastases, offering substantial clinical benefits.